Adaptive clinical trial designs to detect interaction between treatment and a dichotomous biomarker. Issue 3 (8th July 2013) - Zhu, Hongjian; Hu, Feifang; Zhao, Hongyu
Abstract: Biomarkers play a crucial role in the design and analysis of clinical trials for personalized medicine. One major goal of these trials is to derive an optimal treatment scheme based on each patient's biomarker level. Although completely randomized trials may be employed, a more efficient design can be attained when patients are adaptively allocated to different treatments throughout the trial using biomarker information. Therefore, we propose a new adaptive allocation method based on using multiple regression models to study treatment–biomarker interactions. We show that this perspective simplifies the derivation of optimal allocations. Moreover, when implemented in real clinical trials, our method can consolidate all the covariates which may not be related to the treatment–biomarker interaction for a joint analysis. Our general idea can be applied to diverse models to derive optimal allocations. Simulation results show that both the optimal allocation and the proposed design can lead to a more efficient trial. The Canadian Journal of Statistics 41: 525–539; 2013 © 2013 Statistical Society of Canada